From micro to macro: particle physics, gravity and cosmology - Martins, Jéssica Silvano [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
In this thesis we review the particle content of our Universe and its cosmic evolution and show some new physics searches in these two areas. In Part I we present bounds on the energy scale of new physics and couplings of a possible new neutral gauge boson using low energy experiments in the electroweak sector. In Part II we review quantum field theory in curved spacetime and apply some results in cosmology in Part III. In this last part we also show bounds on warm dark matter mass from photometric galaxy surveys.

Nessa tese revisaremos o conteúdo de partículas do nosso Universo e sua evolução cósmica e mostraremos algumas buscas de nova física nessas áreas. Na Parte I apresentamos limites na escala de energia de nova física e acoplamentos de um possível novo bóson de calibre usando experimentos em baixas energias que envolvem a teoria electrofraca. Na Parte II nós revisamos teoria quântica de campos em espaço-tempo curvos e aplicamos alguns resultados em cosmologia na Parte III. Nessa última parte também mostramos limites na massa da matéria escura morna que podem ser obtidos a partir de catálogos de galáxias fotométricos.
Do micro ao macro: física de partículas, gravidade e cosmologia
Keywords: Nova física; Violação de paridade; experimentos de baixa energia; Cosmologia; Inflação; Matéria escura; New physics; Parity violation; low energy experiments; Cosmology; Inflation; Dark matter